IMPLEMENTASI PEMBELAJARAN DARING DI TK AISYIYAH BUSTANUL ATHFAL BASERAH - Febrialismanto; Eva Susanti; Weny Siska Putri Handayani; Enda Putri Melisa Purba; Annisa Selitri Yean (Riau Education Journal, 2021)
The purpose of this research to find out how the implementation of online learning in TK Aisyiyah Bustanul Athfal Baserah and how the teacher's readiness in preparing online learning. The method in this study is a qualitative description. The data collection method in this study used direct observation. The results show that 65% of Aisyiyah Bustanul Athfal Baserah Kindergarten teachers are ready to face online learning. This is influenced by inadequate facilities on the part of teachers and parents and there is still an assumption that online learning is difficult to do. The readiness of teachers to conduct online learning during the Covid-19 pandemic is very necessary. Preparation starts from the lesson plan, communicating with parents, and other supporting facilities.